2021
DOI: 10.22541/au.163664298.87262503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Smell improvement by anti-IgE and anti-IL 5 biologics in patients with CRSwNP and severe asthma– A real life study”

Abstract: Background. Chronic rhinosinusitis with nasal polyps (CRSwNP), characterized by partial (hyposmia) or total (anosmia) loss of smell, is commonly associated with asthma and/or nonsteroidal anti-inflammatory drug-exacerbated respiratory disease (N-ERD), worsens disease severity and quality of life. The objective of this study was to determine whether, in real-life conditions, biological treatments prescribed for severe asthma can improve olfaction in patients with CRSwNP. A further objective was to compare smell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…We would like to make a few comments on areas not addressed by the authors. Meier et al [3] reported similar results 2 years ago, and it is reassuring to see their poor outcome for olfactory function confirmed by Barroso et al [1]. They also compared 3 MABs (mepolizumab, omalizumab, and benralizumab), showing that all 3 treatments had moderate success rates for control of CRS, olfaction, and other symptoms, with mepolizumab performing best.…”
Section: To the Editormentioning
confidence: 76%
See 3 more Smart Citations
“…We would like to make a few comments on areas not addressed by the authors. Meier et al [3] reported similar results 2 years ago, and it is reassuring to see their poor outcome for olfactory function confirmed by Barroso et al [1]. They also compared 3 MABs (mepolizumab, omalizumab, and benralizumab), showing that all 3 treatments had moderate success rates for control of CRS, olfaction, and other symptoms, with mepolizumab performing best.…”
Section: To the Editormentioning
confidence: 76%
“…We read with interest the recent article by Barroso et al [1] on improvement in olfaction in patients with chronic rhinosinusitis with nasal polyposis (CRSwNP) and asthma who received monoclonal antibodies (MABs).…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Обоняние с большей вероятностью улучшалось у пациентов с атопией, более частым применением СГКС коротким курсом и большим размером полипов. Доля пациентов, у которых улучшилось обоняние, была одинаковой в группах как с гиперчувствительностью к нестероидным противовоспалительным препаратам (37%), так и без нее (35,7%) [108]. Таблица 6.…”
Section: хронический риносинусит с полипами носа: основные исследованияunclassified